Peningkatan Ekspresi Vascular Endothel Growth Factor dan Mitogen Activating Protein Kinase Plasenta Tikus yang Dipapar Carbon Black ((INCREASING EXPRESSION ON VASCULAR ENDOTHELIAL GROWTH FACTOR AND MITOGEN ACTIVATING PROTEIN KINASE IN PLACENTA RATS EXPOSE - Hendrawan, Viski Fitri; Widjiati, Widjiati; Susilowati, Suherni; Srianto, Pudji (Jurnal Veteriner, 2017)
Carbon black is one of the components of particulate matter (PM), known as cytotoxic, causing inflammationin the respiratory and cardiovascular system, and able to pass through the placental barrier, which may affect the fetus. The effects caused by pollutants depend on the intensity and time length of the exposure.The objective of this study is to identify Vascular Endothelial Growth Factor (VEGF) and Mitogen Activating Protein Kinase (MAPK) as an indicator of maternal placental inflammation in pregnant rats ( Rattus norvegicus ) exposed to carbon black with immunohistochemical technique. This study was a laboratory experiment with three treatment groups and seven replications using pregnant female white rats ( Rattus norvegicus ). Pregnant female rats were exposed to carbon black with a dosage of 523 mg/m3 and 1064 mg/m3 during pregnancy of day 6 up to day 11. The next phase was the observation and examination of the expressions of VEGF and MAPK by immunohistochemical staining toward placenta of the white rats exposed to carbon black. The result of the study showed an increase in the expression of VEGF in the placenta of the rats exposed to carbon black with a dosage of 523 mg/m3 and 1064 mg/m3 per inhale during the mid-period (6-11) of pregnancy. In addition, there was also an increasein the expression of MAPK on the placenta of the rats exposed to carbon black with a dosage of 523 mg/m3and 1064 mg/m3 per inhale during the mid-period (day 6-11) of pregnancy. In conclusion, the expression of VEGF and MAPK are increased along with the increased dosage of carbon black and age of gestation. ABSTRAK Carbon black merupakan salah satu komponen partikulat matter (PM) yang diketahui bersifat sitotoksik serta menyebabkan terjadinya inflamasi pada sistem pernapasan dan kardiovaskular serta dapat melewati barier plasenta fetus sehingga dapat memengaruhi fetus. Efek yang ditimbulkan oleh polutan tergantung dari besarnya paparan dan lama waktu paparan. Penelitian ini bertujuan untuk mengidentifikasi Vascular Endothel Growth Factor (VEGF) dan Mitogen Activating Protein Kinase (MAPK) sebagai indikator imflamasi pada plasenta maternal tikus ( Rattus norvegicus ) yang dipapar carbon black dengan teknik imunohistokimia. Penelitian ini dilakukan dengan tiga kelompok perlakuan dan tujuh kali ulangan yang menggunakan tikus betina bunting. Tikus betina bunting dipapar dengan carbon black dosis 523 mg/m3 dan 1064 mg/m3 selama kebuntingan hari ke-6 sampai 11. Tahap berikutnya adalah pengamatan dan pemeriksaan ekspresi VEGF dan MAPK dengan pewarnaan imunohistokimia terhadap plasenta tikus putih yang telah dipapar dengan carbon black . Hasil penelitian adalah terjadi peningkatan ekspresi VEGF pada plasenta tikus yang dipapar carbon black dosis 523 mg/m3 dan 1064 mg/m3 per inhalasi selama masa pertengahan (6-11) kebuntingan. Selain itu terjadi peningkatan ekspresi MAPK pada plasenta tikus yang dipapar carbon black dosis 523 mg/m3 dan 1064 mg/m3 per inhalasi selama masa pertengahan(6-11) kebuntingan. Simpulan penelitian ini adalah ekspresi VEGF dan MAPK meningkat seiring dengan peningkatan dosis carbon black dan umur kebuntingan.
Keywords: carbon black,mitogen activating protein kinase, vascular endothel growth factortrophoblast placenta